2022
DOI: 10.1155/2022/5545319
|View full text |Cite
|
Sign up to set email alerts
|

Role of T Regulatory Cells and Myeloid-Derived Suppressor Cells in COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) has been raised as a pandemic disease since December 2019. Immunosuppressive cells including T regulatory cells (Tregs) and myeloid-derived suppressor cells (MDSCs) are key players in immunological tolerance and immunoregulation; however, they contribute to the pathogenesis of different diseases including infections. Tregs have been shown to impair the protective role of CD8+ T lymphocytes against viral infections. In COVID-19 patients, most studies reported reduction, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 120 publications
(145 reference statements)
1
5
0
2
Order By: Relevance
“…Under normal conditions, Foxp3 + Tregs migrate into inflamed tissues to suppress inflammatory responses to exert immunosuppressive effects and accelerate tissue repair [ 15 , 138 ]. In pre-existing respiratory comorbidities such as COVID-19, which leads to the disruption of the immune system, exacerbated inflammation which is partly due to the decreased expression of Tregs or defects in these cells results in weakening the Tregs effects of inflammatory inhibition, causing an imbalance in Treg/Th17 ratio, and increasing the risk of respiratory failure [ 137 , 139 , 140 , 141 ]. Since our data showed that the smoke and morphine combination promote weakened, plastic/dysfunctional Tregs and Treg plasticity toward Th17 cells, smoke plus morphine in combination in pre-existing respiratory co-morbidities such as COVID-19 will exacerbate inflammation and increase the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, Foxp3 + Tregs migrate into inflamed tissues to suppress inflammatory responses to exert immunosuppressive effects and accelerate tissue repair [ 15 , 138 ]. In pre-existing respiratory comorbidities such as COVID-19, which leads to the disruption of the immune system, exacerbated inflammation which is partly due to the decreased expression of Tregs or defects in these cells results in weakening the Tregs effects of inflammatory inhibition, causing an imbalance in Treg/Th17 ratio, and increasing the risk of respiratory failure [ 137 , 139 , 140 , 141 ]. Since our data showed that the smoke and morphine combination promote weakened, plastic/dysfunctional Tregs and Treg plasticity toward Th17 cells, smoke plus morphine in combination in pre-existing respiratory co-morbidities such as COVID-19 will exacerbate inflammation and increase the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) and macrophages can engulf virus-infected cells during the early stages of SARS-CoV-2 infection, triggering T-cell responses through antigen presentation. CD4 + T cells then drive B cells to make virus-specific antibodies, while cytotoxic CD8 + T cells attack virus-infected cells [ 48 ]. In addition, it was reported that more than 70% of COVID-19 convalescent patients had SARS-CoV-2-specific T cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is diagrammed in Figure 1 . Elevated NLR and the emergency granulopoiesis typical of severe COVID-19 are related, and are inextricably linked an increase in MDSC, contributing to the characteristic immunosuppression of ARDS of any origin, including that of COVID-19 [ 31 , 33 , 34 ].…”
Section: Rationalementioning
confidence: 99%
“…MDSC numbers and immune suppressive activity increase in direct proportion to the NLR and become an important immunosuppressive element during severe COVID-19 [ 33 , 34 , 35 , 36 , 37 , 38 ]. Absolute neutrophil numbers and the NLR exist and function within a neutrophil-centered interacting multi-component inflammation system.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation